Validity and reliability “K² REBT” group counseling module depression among students - Ishak, Nor Asikhin; Ishak, Nurul Huda; Khalid, Mohamad Sukeri (Institute of Advanced Engineering and Science, 2025)
Depression among teenagers, especially students, is an increasing concern with serious consequences, including criminal behavior and suicide. This study develops a rational emotive behavior therapy (REBT) counseling module aimed at reducing irrational beliefs and enhancing the cognitive, emotional, and behavioral well-being of depressed students. The module comprises four sub-modules: self-acceptance, feelings, beliefs, and challenging, based on established REBT principles. The 30 students diagnosed with depression participated in reliability testing, while content validity was assessed by five experts, yielding a high validity quotient of 0.930. The module’s reliability was confirmed with a Cronbach’s alpha of 0.964, indicating strong internal consistency. These findings suggest that the REBT Module is a highly valid and reliable tool for improving coping strategies and alleviating depression among students, making it a valuable addition to school counseling programs.